TBI: SURGICAL APPROACH AND INTENSIVE CARE UNIT MANAGEMENT AFTER THE PROCEDURE (Editora Impacto Científico, 2025)
Traumatic brain injury (TBI) is one of the leading causes of morbidity and mortality worldwide, particularly affecting young adults due to traffic accidents, falls, and assaults. It is characterized by brain injuries of varying severity, which can be mild, moderate, or severe according to the Glasgow Coma Scale (GCS). The present study conducted a narrative literature review from 2020 to 2025 in the PubMed database, using the descriptors “traumatic brain injury,” “surgical approach,” and “intensive care unit.” Ten articles were selected after applying inclusion and exclusion criteria. The results indicate that surgical treatment is essential in cases of intracranial hemorrhages, refractory cerebral edema, and depressed fractures, with emphasis on procedures such as decompressive craniectomy and hematoma evacuation. Postoperative management in the Intensive Care Unit (ICU) is decisive for prognosis, requiring rigorous monitoring of intracranial pressure, cerebral perfusion, and control of secondary complications. The role of the multiprofessional team and the application of evidence-based protocols, such as those from the Brain Trauma Foundation, proved fundamental to reducing mortality and promoting functional rehabilitation. It is concluded that the integration of early diagnosis, timely surgical intervention, and continuous intensive support is critical for neurological recovery and improving the quality of life of patients with TBI.DOI: https://doi.org/10.56238/edimpacto2025.091-004